2021
DOI: 10.3389/feduc.2021.639294
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Predictors of Response to Intervention With GraphoGame Rime

Abstract: This study explores the neurocognitive predictors of response to intervention with GraphoGame Rime (GG Rime), an adaptive software game designed to aid the learning of English phonics. A cohort of 398 children (aged 6–7 years) who had participated in a recent randomised controlled trial (RCT) of GG Rime in the United Kingdom were studied. Half were randomly assigned to play GG Rime and the other half were assigned to Business As Usual (BAU). A series of pretests were given prior to the intervention to all part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…At least for the GL in-game assessment tasks, there were differences in game effectiveness with those children with better pre-existing English literacy skill seemingly benefitting more. These findings are in line with previous GL English Rime studies which have found that existing phoneme awareness skill is predictive of response to GL (Wilson et al, 2021) and those children who do respond to GL seem to make gains (Ahmed et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…At least for the GL in-game assessment tasks, there were differences in game effectiveness with those children with better pre-existing English literacy skill seemingly benefitting more. These findings are in line with previous GL English Rime studies which have found that existing phoneme awareness skill is predictive of response to GL (Wilson et al, 2021) and those children who do respond to GL seem to make gains (Ahmed et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Teachers found GL Rime easy to implement, engaging, and motivating, however, there was no evidence of improved reading outcomes over business-as- showed significantly higher gains and it was concluded that GL is more effective than business-as-usual in developing English phonics (Ahmed et al, 2020). Wilson et al (2021) recently re-examined the same data set to better understand the types of children who best respond to GL intervention as indicated by game progress. They found that phonological skills and executive functioning skills were the strongest unique predictors of game progress.…”
Section: Grapholearnmentioning
confidence: 99%
“…Importantly, the results suggested that in response to the BSLA teaching, children were learning to use their enhanced phonic and phonological awareness knowledge in decoding and encoding written words, as evidenced by their significantly improved non-word reading and spelling performance. Recently, Wilson et al (2021) also reported positive outcomes from explicit teaching via a digital game format that focused children's attention on word decoding and encoding skills. In their study, they observed children's responses to a digital game intervention that they played for 10-15 min daily for 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…This paper focuses on the children's development of phoneme awareness skills and the transfer of these skills to reading and spelling in response to the BSLA teaching within the children's first year at school. A child's phonological awareness ability has consistently been shown to be a strong protective factor in supporting children's early reading success (Wilson et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Bezerra-Mota et al, 2016;Buono et al, 2020). The secondary stage was explored in the United Kingdom and investigated whether verbal and/or visuospatial working memory tasks correlate with reading and mathematics performance (Giofré et al, 2018;Wilson et al, 2021). In the university context, only one study contributed to demonstrate the influence of memory and emotion on reading habits (Álvarez et al, 2021).…”
Section: Cognitive Neuroeducational Principlementioning
confidence: 99%